2010
DOI: 10.1021/ma101565u
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Ligand-Dependent Mechanistic Changes in Nickel-Catalyzed Chain-Growth Polymerizations

Abstract: The mechanisms for Ni(dppp)Cl2-catalyzed chain-growth polymerization of 4-bromo-2,5-bis(hexyloxy)phenylmagnesium chloride and 5-bromo-4-hexylthiophen-2-ylmagnesium chloride were investigated. A combination of rate and spectroscopic studies revealed that transmetalation is the rate-determining step of the catalytic cycle for both monomers. 31P NMR spectroscopic studies revealed that a Ni(II)−aryl halide and a Ni(II)−thienyl halide are the catalyst resting states. In addition, LiCl was found to alter the arene p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
100
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 87 publications
7
100
0
Order By: Relevance
“…[63,78] For the dppp-supported KCTP, Ni II -monoaryl intermediates that precede the TM step were observed as the catalyst resting states (7, Scheme 4). [78] This result is in accordance with kinetic studies of McCullough and coworkers [22] and Lamps and Catala et al [79] for Ni(dppp)Cl 2 -catalyzed KCTP, who found that the rate of polymerization is first-order on monomer concentration, suggesting TM as the rate-determining step. In contrast, for dppe-supported polymerizations, Ni II -biaryl complexes preceding the RE step (8, Scheme 4) were observed as the catalyst resting states, which suggests RE as the ratedetermining step.…”
Section: Chain-propagationmentioning
confidence: 99%
See 1 more Smart Citation
“…[63,78] For the dppp-supported KCTP, Ni II -monoaryl intermediates that precede the TM step were observed as the catalyst resting states (7, Scheme 4). [78] This result is in accordance with kinetic studies of McCullough and coworkers [22] and Lamps and Catala et al [79] for Ni(dppp)Cl 2 -catalyzed KCTP, who found that the rate of polymerization is first-order on monomer concentration, suggesting TM as the rate-determining step. In contrast, for dppe-supported polymerizations, Ni II -biaryl complexes preceding the RE step (8, Scheme 4) were observed as the catalyst resting states, which suggests RE as the ratedetermining step.…”
Section: Chain-propagationmentioning
confidence: 99%
“…For example, 1 polymerizes much faster at room temperature with dppe as the ligand than with dppp in a broad range of monomer concentrations (0.01-0.5 M), whereas the two rates are comparable at 0 8C. [63,78] Among the intermediates shown in Scheme 4, the Ni(0) complex 6 is only one that has not been observed spectroscopically, indicating its short-lived nature. Despite of this, we believe that Ni(0) complexes not only exist, but also play an important role in KCTP since they are the base of a fascinating catalyst ''ring-walking'' (RW) process which is discussed in the following.…”
Section: Chain-propagationmentioning
confidence: 99%
“…The original Grignard metathesis polymerization scheme, reported by McCullough, suggested that following reductive elimination, the growing polymer associates nondiffusively with the Ni catalyst. It is now recognized that the mechanism proceeds instead via a Ni-polymer π-complex, [23][24][25] The Ni catalyst does not, however remain associated with a single chain end, as substantial evidence exists to support a chain walking process, allowing for bidirectional propagation during CTP. 26,27 Motivated by these reports (as well as those suggesting Ni 0 diffusion and catalyst resting states), 23,28 and inspired by our understanding of the ATRP mechanism, we consider periods of deactivation and subsequent reactivation within the GRIM polymerization mechanism.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…31 The rates of reductive elimination and oxidative addition (k re and k oa , respectively) were inferred from kinetic studies which indicate the rate limiting step in Ni(dppp)Cl 2 -catalyzed synthesis of poly(3-hexylthiophene) to be transmetallation (k tm ), as evidenced by a first order rate dependence on both monomer and catalyst. 6,8,24,32 Changing the catalyst to Ni(dppe)Cl 2 results in zeroth order dependence on monomer concentration and first order dependence on the concentration of catalyst, indicating that reductive elimination is the rate limiting step. 23 In the entire set of simulations the value of k tm has been set to unity and used as a reference value for all remaining rate constants.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…To date, the π-complex has not been isolated and, indeed, there has been no direct spectroscopic evidence of its existence. 31 P and 1 H studies of the polymerization mixture, using either Ni(dpppe)Cl 2 or Ni(dppp)Cl 2 , have shown that the catalyst resting state is either the Ni(II) complex prior to reductive elimination for Ni(dpppe)Cl 2 [52], or the Ni(II) complex prior to transmetallation for Ni(dppp)Cl 2 [53], with no evidence for a Ni(0) π-complex having been observed. In addition to this change being the rate-limiting step from reductive elimination to transmetallation, it also confirms that the nature of the catalyst ligand has an important mechanistic role in the polymerization.…”
Section: Polythiophenes By Kumada Cross-couplingmentioning
confidence: 99%